Comparación de la aplicación de la técnica de restauración atraumatica (art) con un método tradicional: presentación de casos clínicos en niños de 5 a 9 años - Gallegos Viera, Débora Carla (2015)
The aim of this study was to compare the application of two restorative techniques widely used in schools patients such as atraumatic restoration technique (ART), compared with the conventional technique of restoration with rotary instruments and high-speed cutter, which was observed acceptance to dental treatment in pediatric patients ranging from the ages of 5-9 years, raising the hypothesis that children presented greater acceptance to the treatment of ART, the study sample was comprised of 15 children for group A and 15 children for group B. the treatment for group A was the treatment of atraumatic restoration, and the group B was the conventional technique of restoration with rotary instruments and strawberry using as glass ionomer restorative material Ketac Molar (3M-ESPE) to both groups, data were collected at the School of Basic education "Nicolas Javier Gorivar" Quito-Ecuador, where they rated the facial treatment with a scale indicating whether or not the treatment performed liked. Then the data were taken to statistical analysis, Data analysis showed the value of P, p: 0.0086 showing that there is a significant statistical difference between the two treatments, group A had an acceptance of 80% and group B had an acceptance of 33 33 percent to the conclusion that when comparing the two restorative techniques were group A match atraumatic restoration treatment (ART) the largely accepted by scholars patients.